Search for dormant black holes in ellipsoidal variables – II. A binary modified minimum mass ratio. Issue 2 (15th April 2021) - Gomel, Roy; Faigler, Simchon; Mazeh, Tsevi
ABSTRACT: This is the second of a series of papers that focuses on searching large sets of photometric light curves for evidence of close binaries with a dormant black hole, and, in some cases, a dormant neutron star. The detection of such a binary is based on identifying a star that displays a large ellipsoidal periodic modulation, induced by tidal interaction with its companion. Based on the observed ellipsoidal amplitude and the primary mass and radius, one can derive a minimum mass ratio of the binary. A binary with a minimum mass ratio significantly larger than unity might be a candidate for having a dormant compact-object companion. Unfortunately, the photometric search is hampered by the fact that in many cases the primary mass and radius are not well known. In this paper we present a simple approach that circumvents this problem by suggesting a robust modified minimum mass ratio, assuming the primary fills its Roche lobe. The newly defined modified minimum mass ratio is always smaller than the minimum mass ratio, which is, in its turn, smaller than the actual mass ratio. Therefore, binaries with a modified minimum mass ratio larger than unity are candidates for having a compact-object secondary.